Cross-cultural adaptation and validation of the Chinese version of the 25-question Geriatric Locomotive Function Scale in patients undergoing total knee arthroplasty - Zhipeng Tai; Zhipeng Tai; Dongping Wan; Shuxin Yao; Shaohua Miao; Shaohua Miao; Qiang Zan; Yanchen Tan; Jianbing Ma; Chao Xu (Frontiers in Medicine)
BackgroundKnee osteoarthritis (KOA) is prevalent among the elderly, often necessitating total knee arthroplasty (TKA) for severe cases. However, traditional assessment tools primarily focus on pain and physical function, neglecting the psychosocial aspects that influence postoperative satisfaction. The 25-question Geriatric Locomotive Function Scale (GLFS-25) is a comprehensive measure of locomotor function, however, it has limited validation within populations in Mainland China.ObjectivesThis study aimed to translate, cross-culturally adapt, and validate the Chinese version of the GLFS-25 (GLFS-25CV) for evaluating postoperative outcomes in TKA patients with KOA.MethodsFollowing established guidelines, the English GLFS-25 was both forward- and back-translated, subjected to expert review, and pretested in 30 patients. End-stage KOA patients scheduled for primary unilateral TKA were then recruited, with a subset completing the GLFS-25CV twice, one week apart, to assess test-retest reliability. Exploratory factor analysis (EFA) was conducted to evaluate structural validity, while convergent validity was assessed through Pearson correlations with the Oxford Knee Score (OKS), the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and the 5-Level EuroQol Five-Dimensional Questionnaire (EQ-5D-5L). Internal consistency was evaluated using Cronbach’s α, and standard deviations (SD) were calculated. Additionally, floor and ceiling effects were analyzed based on score distributions.ResultsA total of 295 participants completed the study. Both the four-factor model identified by EFA, which explained 58% of the total variance, and the strong correlations with the OKS (rho = 0.85), the WOMAC (rho = 0.77), and the EQ-5D-5L (rho = 0.66) collectively confirm the excellent validity of the GLFS-25CV. Internal consistency was excellent (Cronbach’s α = 0.94, SD > 0.85), and test-retest reliability (ICC = 0.94–0.97) was also strong, confirming its overall reliability. Neither floor nor ceiling effects were significant, and no participants reported difficulty completing the instrument.ConclusionThe GLFS-25CV is a reliable, valid, and user-friendly tool for assessing knee function in individuals in mainland China undergoing TKA for KOA. By incorporating both physical and psychosocial domains, it offers a comprehensive evaluation that is well-suited for both clinical practice and research applications.